HIT AND RUN: A Phenomenological Study of Manufacturer Experience in E-Commerce Transactions with the Pre-Order System from a Fiqh Muamalah Perspective - Asnita, Dessy; Mudrika, Syarifah (Al-Muamalat: Jurnal Ekonomi Syariah, 2025)
This research examines clothing manufacturers located in Bandung and Bekasi and a distributor in Medan to analyze the impact of the "hit-and-run" phenomenon in e-commerce transactions using the Pre-Order (PO) system. In this model, buyers place orders for products but frequently fail to complete payments or disappear after the items have been produced. This issue leads to stock accumulation, disrupts financial flows, and results in significant economic losses for manufacturers. This study aims to analyze the impact of the "hit-and-run" phenomenon on clothing manufacturers and explore potential solutions to mitigate it. The research method used is a qualitative approach with a descriptive phenomenological type. The research findings show that the "hit-and-run" phenomenon negatively affects manufacturers, creating uncertainty in their business operations. The implications of this study highlight the importance of developing more cautious policies in accepting orders and implementing effective communication strategies to minimize the risk of losses. This research provides an in-depth understanding of the dynamics of e-commerce transactions with the PO system and valuable insights for manufacturers in managing risks and improving their business continuity in a competitive market.